UPAYA MENINGKATKAN KESADARAN GENDER KAUM MUDA MELALUI PESAN KESETARAAN GENDER DI MEDIA SOSIAL INSTAGRAM - Annisa Anindya; Alna Hanana; Novi Elian (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
Young people are the driving force in voicing these various messages of gender equality on social media. The point of view also departs from the audience's perspective as the center of the campaign carried out on this social media and its activities. This study examines young people's understanding regarding experience, knowledge, and awareness of gender and how young people's efforts to voice gender awareness using social media. At first, these young people used Instagram to find information regarding the issue of gender equality. Slowly, after understanding this, their information is getting more diverse and condensed. They initially used Instagram social media for introductions, which became a communication channel to spread understanding about gender to the broader public. This research shows that young people have gender awareness in understanding gender which is essential to their immediate environment and accelerates the need for gender awareness in further discourse. On this basis, we conclude that Instagram is a bridge in paving the way for young people to access various and actual information. Instagram helps them spread messages of gender equality through light and engaging, concise information, which then becomes the subject of discussion for advanced interactions via other social media platforms.